Mechanisms of Cardiovascular Protection Associated with Intermittent Hypobaric Hypoxia Exposure in a Rat Model: Role of Oxidative Stress - Garcia-Herrera, C; Cañas-Quezada, D (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
More than 140 million people live and works (in a chronic or intermittent form) above 2500 m worldwide and 35 million live in the Andean Mountains. Furthermore, in Chile, it is estimated that 55,000 persons work in high altitude shifts, where stays at lowlands and interspersed with working stays at highlands. Acute exposure to high altitude has been shown to induce oxidative stress in healthy human lowlanders, due to an increase in free radical formation and a decrease in antioxidant capacity. However, in animal models, intermittent hypoxia (IH) induce preconditioning, like responses and cardioprotection. Here, we aimed to describe in a rat model the responses on cardiac and vascular function to 4 cycles of intermittent hypobaric hypoxia (IHH). Twelve adult Wistar rats were randomly divided into two equal groups, a four-cycle of IHH, and a normobaric hypoxic control. Intermittent hypoxia was induced in a hypobaric chamber in four continuous cycles (1 cycle = 4 days hypoxia + 4 days normoxia), reaching a barometric pressure equivalent to 4600 m of altitude (428 Torr). At the end of the first and fourth cycle, cardiac structural, and functional variables were determined by echocardiography. Thereafter, ex vivo vascular function and biomechanical properties were determined in femoral arteries by wire myography. We further measured cardiac oxidative stress biomarkers (4-Hydroxy-nonenal, HNE; nytrotirosine, NT), reactive oxygen species (ROS) sources (NADPH and mitochondrial), and antioxidant enzymes activity (catalase, CAT; glutathione peroxidase, GPx, and superoxide dismutase, SOD). Our results show a higher ejection and shortening fraction of the left ventricle function by the end of the 4th cycle. Further, femoral vessels showed an improvement of vasodilator capacity and diminished stiffening. Cardiac tissue presented a higher expression of antioxidant enzymes and mitochondrial ROS formation in IHH, as compared with normobaric hypoxic controls. IHH exposure determines a preconditioning effect on the heart and femoral artery, both at structural and functional levels, associated with the induction of antioxidant defence mechanisms. However, mitochondrial ROS generation was increased in cardiac tissue. These findings suggest that initial states of IHH are beneficial for cardiovascular function and protection. © 2018 by the authors. Licensee MDPI, Basel, Switzerland.